2016
DOI: 10.1097/aln.0000000000000983
|View full text |Cite
|
Sign up to set email alerts
|

IV and Perineural Dexmedetomidine Similarly Prolong the Duration of Analgesia after Interscalene Brachial Plexus Block

Abstract: Background Perineural and IV dexmedetomidine have each been suggested to prolong the duration of analgesia when administered in conjunction with peripheral nerve blocks. In the first randomized, triple-masked, placebo-controlled trial to date, the authors aimed to define and compare the efficacy of perineural and IV dexmedetomidine in prolonging the analgesic duration of single-injection interscalene brachial plexus block (ISB) for outpatient shoulder surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
139
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(149 citation statements)
references
References 67 publications
6
139
0
4
Order By: Relevance
“…A clinical trial investigated the perineural and intravenous addition of dexmedetomidine 0.5 µg/kg vs placebo to an interscalene nerve block using 15 mL ropivacaine 3. They reported that both perineural and systemic dexmedetomidine prolonged the duration of the nerve block significantly, which is in support of our results.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A clinical trial investigated the perineural and intravenous addition of dexmedetomidine 0.5 µg/kg vs placebo to an interscalene nerve block using 15 mL ropivacaine 3. They reported that both perineural and systemic dexmedetomidine prolonged the duration of the nerve block significantly, which is in support of our results.…”
Section: Discussionsupporting
confidence: 88%
“…In healthy volunteers, a dramatic effect was observed when dexmedetomidine was administered perineurally, but also a lesser result when administered intravenously 2. In patients, systemic and perineural dexmedetomidine prolonged the duration of interscalene nerve blocks similarly 3. These trials, however, used a suboptimal dose of dexmedetomidine4 and lacked control of systemic effects: the extended block duration observed in the perineural groups may have been caused by absorption and re-distribution of the perineural dexmedetomidine triggering systemic effects and not by a perineural mechanism 2 3…”
Section: Introductionmentioning
confidence: 96%
“…The efficacy of IV Dex in prolonging the analgesic duration of brachial plexus block for shoulder surgery was assessed in a randomized clinical trial and it was found that Dex reduced the pain and opioid consumption up to 8 hours postoperatively and did not prolong the duration of the motor blockade (22).…”
Section: Discussionmentioning
confidence: 99%
“…Es de destacar que hay algunos estudios de que la dexmedetomidina i.v. puede ser tan efectiva como la perineural para prolongar la analgesia y reducir el consumo de opioides en el período postoperatorio temprano (73).…”
Section: α-Agonistasunclassified